2015
DOI: 10.1007/s10545-015-9896-7
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent acute liver failure due to NBAS deficiency: phenotypic spectrum, disease mechanisms, and therapeutic concepts

Abstract: Mutations in NBAS cause a complex disease with a wide clinical spectrum ranging from isolated RALF to a multisystemic phenotype. Thermal susceptibility of the syntaxin 18 complex is the basis of fever dependency of ALF episodes. NBAS deficiency is the first disease related to a primary defect of retrograde transport. Identification of NBAS deficiency allows optimized therapy of liver crises and even prevention of further episodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
141
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(153 citation statements)
references
References 18 publications
6
141
0
1
Order By: Relevance
“…[1] ILFS type 2 is caused by a mutation in the NBAS gene on the chromosome 2p24. [2] ILFS type 1 is caused by mutation in the Leucyl-tRNA synthetase (LARS) gene on the chromosome 5q32. [3]…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[1] ILFS type 2 is caused by a mutation in the NBAS gene on the chromosome 2p24. [2] ILFS type 1 is caused by mutation in the Leucyl-tRNA synthetase (LARS) gene on the chromosome 5q32. [3]…”
Section: Discussionmentioning
confidence: 99%
“…and Staufner et al . [12] have examined 16 patients with NBAS mutation. They showed that phenotypic spectrum of NBAS deficiency ranges between isolated recurrent acute liver failure and multisystemic disease, which includes short stature, skeletal dysplasia, optic atrophy, and immunological abnormalities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Antipyretic therapy and induction of anabolism including glucose and parenteral lipids may ameliorate the course of liver crises in certain patients as has been noted in NBAS deficiency. 34 Liver transplantation may be indicated in some cases and has been performed in patients with mitochondrial disease. Survival after liver transplantation in some mitochondrial patients approaches that of transplanted patients without mitochondrial disease -although some patients may fare worse (POLG-related disease).…”
Section: Gastroenterologymentioning
confidence: 99%